Enforcing public takeover regulation: Reconciling public and private interests - WAN, Wai Yee (Institutional Knowledge at Singapore Management University, 2019)
Takeover regulation in the UK, Hong Kong and Singaporerelies on takeover codes and takeover panels. However, parties aggrieved by thedecisions of the panels may sometimes challenge them in the courts, giving riseto the potential of overlapping jurisdictions. The problem is compounded by twofactors: the enforcement of the takeover codes can have substantiveimplications on the parties’ ability to enforce their rights in courts, and takeoverpanels and courts assess matters differently. This article argues that thereneeds to be a clearer delineation between the potentially overlappingjurisdictions of the takeover panels and the courts.